2019
DOI: 10.15171/bi.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

In silico, in vitro: antioxidant and antihepatotoxic activity of gnetol from Gnetum ula Brongn

Abstract: Introduction: Gnetum ula is a notable medicinal plant used to cure various ailments. The stem part of the plant is used traditionally to treat jaundice and other disorders. The present work is to investigate the in vitro hepatoprotective and antioxidant activity of ethanol extract of stem of G. ula (GUE) and its isolated compound gnetol. Methods: Column chromatography was carried out for GUE and various column fractions were obtained. DPPH and reducing power assays were performed for GUE and column fractions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…2 Among hydroxylated stilbenes, information about the activity and characterization of gnetol (trans-2 0 ,3,5,6 0 -tetrahydroxystilbene) is scarce and is mainly related to Gnetum plant extracts instead of the isolated compound. [7][8][9] Even so, it has been described that gnetol inhibits cyclooxygenase-1, tyrosinase, acetylcholinesterase, histone deacetylase, and cytochrome P450s 2C9 and 3A4, which could indicate that it has anti-inflammatory, anti-thrombotic, cardioprotective and anti-cancer activity. 10 Pharmacokinetic studies have shown that, despite being less bioavailable than resveratrol, gnetol has a longer half-life after oral administration in rats.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among hydroxylated stilbenes, information about the activity and characterization of gnetol (trans-2 0 ,3,5,6 0 -tetrahydroxystilbene) is scarce and is mainly related to Gnetum plant extracts instead of the isolated compound. [7][8][9] Even so, it has been described that gnetol inhibits cyclooxygenase-1, tyrosinase, acetylcholinesterase, histone deacetylase, and cytochrome P450s 2C9 and 3A4, which could indicate that it has anti-inflammatory, anti-thrombotic, cardioprotective and anti-cancer activity. 10 Pharmacokinetic studies have shown that, despite being less bioavailable than resveratrol, gnetol has a longer half-life after oral administration in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Following the completion of the scheduled docking runs, the variable conformations of the protein with ligands were obtained as binding methods with their respective binding affinity. The stable confirmation mode with the optimum best interaction was selected and was the one that represented the lowest binding affinity; the same was picked and aligned alongside the receptor structure for further investigation [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…After the successful completion of the docking runs, different conformations of the ligands known as binding modes were obtained with their respective binding affinity and the stable one which happens to be the one with the lowest binding affinity was picked and aligned with receptor structure for further analysis. 39 , 40 …”
Section: Methodsmentioning
confidence: 99%